Metode Forward Chaining Untuk Mendiagnosa Kerusakan Mesin Mobil Toyota Innova Berbasis Web - Haryanto Haryanto; Eka Wulansari Fridayanthie; Jazmi Adlan Nadhir; Azis Sukma Dhiana; Mochamad Nandi Susila (Universitas Bina Sarana Informatika Kota Sukabumi, 2022)
The growing development of the automotive industry in Indonesia has an impact on increased car sales. More and more people are buying cars because they have become daily transportation. Damage experienced in the car is handled by experts or expert technicians. Diagnosis of damage is carried out by a technician based on signs of initial damage to the car. This encourages experts to develop new computer systems to support human work. The development of computers today has undergone many very rapid changes, along with the increasing and complex human needs. then we need a method or system that can diagnose damage to the car. One of them is by utilizing artificial intelligence technology. One sub-field of artificial intelligence is an expert system. By utilizing expert system technology can be produced a system to diagnose car engine damage. This expert system discusses the diagnosis of web-based Toyota Innova damage using the forward chaining method. With the aim of helping the community to diagnose the damage to the Toyota Innova car engine.